Assessment of the occurrence of postural abnormalities in children aged 10-12 practicing various sports disciplines - Dagna Balińska; Piotr Ożóg; Magdalena Weber-Rajek; Agnieszka Radzimińska (Journal of Education, Health and Sport)
Background: The increase in the prevalence of children with poor posture might be a result of decreased physical activity due to a sedentary lifestyle. Observing body posture is a crucial component of a physical examination. The examination can be performed objectively, for instance, with the aid of specific instruments, or subjectively, through visual inspection of the alignment of individual body parts in relation to one another. Objectives: The aim of our study was to assess the occurrence of postural abnormalities in children aged 10-12 who are physically active and practice various types of sports.Methods: The study group comprised 47 children aged 10–12 who were physically active and engaged in various sports activities. Participants have been visually examined based on a postural deficit chart derived from Kasperczyk’s criteria. Results: Our research showed that volleyball had the highest percentage of postural abnormalities, accounting for 33% of all postural irregularities in this group, while the lowest percentage was observed in children who practiced swimming, at 7%. Conclusion: Physical activity may have an impact on the occurrence of postural defects in early school children. Further research is needed to expand our findings to include the outcomes of objective posture assessment methods.